SYNTHESIZING AND EVALUATION OF NEW EDM ELECTRODE MATERIALS FOR MACHINING HARDENED DIE-STEEL USING TAGUCHI TECHNIQUE - MAHAMAT, AL TJDJANI ZAKARIA (2012)
By using Electrical discharge machining (EDM) it is possible to machine any which material that are difficult to machine by conventional machining technique as long as it is electrically conductive. The performance of EDM is highly depending on the type of electrode being used, the power supply system, and the dielectric system. CopperTungsten electrode combines the higher melting point of tungsten with the good electrical and thermal conductivity of copper but it is difficult to be manufacture due to variation of melting point and zero miscibility of Copper with Tungsten. Thus, new modified Copper-Tungsten electrodes were synthesized taking into consideration the variety of melting point and zero miscibility. Ball milling was used to synthesize the new electrode material due to the possibility to overcoming the problems encountered in alloying materials have a large variation in melting temperature or low miscibility at low temperatures. Taguchi method is the main statistical tool used to design and analyse ball milling and machining process. Material removal rate and electrode wear are the parameters used for comparing the performance between the existing Copper-Tungsten and new developed electrode. Miiling results show a clear change in the thickness of crystalline and d-spacing of the milled powder. Machining variables selection shows that the gap voltage, peak current and pulse on time are the most important variables contribute on material removal rate MRR, electrode wear EW and surface roughness Ra. The performances of Cu-WC-Si electrode in machining of hardened die steel shows an improvement in MRR and EW compared with that achieved by using Cu-W electrode when it is milled for less than I 0 h. On the other hand, the performance of 5 h and I 0 h milling time Cu-WC-Ti and Cu-WC-Ti-Si show clear improvement in the electrode wear but in the cost of MRR. Cu-WC-Si show the lowest possible tool wear ratio TWR compared with Cu-WC-Ti and Cu-WC-Ti-Si.